2007
DOI: 10.1089/end.2006.0275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Results of Shockwave Lithotripsy for Renal Calculi in Upper, Middle, and Lower Calices

Abstract: We recommend SWL as the first choice for treatment of stones <200 mm2 in the upper and middle calices. Extracorporeal lithotripsy is one of the options for lower-caliceal stones <200 mm2 but has high re-treatment and auxiliary-procedure rates in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
2
9
0
2
Order By: Relevance
“…12 Present study also matches with the study of Turna B, et al in terms of the stone-free rates for stones in the upper, middle, and lower calices. 13 It also matches with study of Sumino Y et al, who reported an overall stone clearance rate of 54% for lower pole calyceal stones and with the study of Pacik D et al who's success rate of lower pole calculi is 61.3%. 14,15 ESWL success for lower pole calculi is slightly lower than the results of the study of Gupta et al who achieved an overall stone clearance at 6 months of about 72% for lower calyceal stones.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12 Present study also matches with the study of Turna B, et al in terms of the stone-free rates for stones in the upper, middle, and lower calices. 13 It also matches with study of Sumino Y et al, who reported an overall stone clearance rate of 54% for lower pole calyceal stones and with the study of Pacik D et al who's success rate of lower pole calculi is 61.3%. 14,15 ESWL success for lower pole calculi is slightly lower than the results of the study of Gupta et al who achieved an overall stone clearance at 6 months of about 72% for lower calyceal stones.…”
Section: Discussionsupporting
confidence: 89%
“…The final outcome of the present study matches with the study of Turna B, et al in which success of ESWL for calculi <10 mm and between 11-20 mm was 91.2% and 65.5% respectively (p = 0.001). 13 AbdelKhalek M et al found that size was significant independent predictor of ESWL outcome (p < 0.001). 8 In the study of Wang L et al 16 ESWL outcome was not significant for the calculi >12 mm, which is in contradiction to the present results in which outcome for calculi between 11-20 mm was significant at 84.2%.…”
Section: Discussionmentioning
confidence: 98%
“…Nowadays, these stones can be treated with retrograde intrarenal surgery (RIRS), ESWL, and percutaneous nephrolithotomy. [9,10] ESWL, and RIRS can be successfully performed for stones smaller than 2 cm in diameter, and increased stone size decreases success rates of both treatment modalities. [11] Besides, narrow, and elongated neck of the calyx containing the stone prevents spontaneous passage of fragmented stone particles.…”
Section: Discussionmentioning
confidence: 99%
“…[4] However, SWL seems to be affected by stone location, with documented stone free rates of 82.8%, 83.4% and 67.5% for upper, middle and lower calices, respectively. [5] Improvements in endoscope design, optical quality and laser devices have made fURS an effective option for the treatment of kidney stones. The high stone-free rates combined with low rate of complications have resulted in the widespread usage of fURS.…”
Section: Introductionmentioning
confidence: 99%